Re-establishment of Psidium macahense (Myrtaceae, Myrteae), an endemic species from the Brazilian Atlantic Forest - Tuler, Amélia Carlos; Carrijo, Tatiana Tavares; Sheu, Yumi; Ferreira, Marcia Flores Da Silva; Peixoto, Ariane Luna (Phytotaxa, 2019)
Psidium macahense, an endemic species of Myrtaceae from the Brazilian Atlantic Forest, has recently been treated as a synonym of Psidium brownianum. Using a combination of molecular and morphological analyses the specific status of P. macahense is herein reinstated. A lectotype is designated for Psidium macahense, and a detailed description of the species with, illustrations and photographs to facilitate identification, is provided.